Sensory quiescence induces a cell-non-autonomous integrated stress response curbed by condensate formation of the ATF4 and XRP1 effectors - Shashank Shekhar; Charles Tracy; Peter V. Lidsky; Raul Andino; Katherine J. Wert; Helmut Krämer (Nature Communications)
Abstract Sensory disabilities have been identified as significant risk factors for dementia but underlying molecular mechanisms are unknown. In different Drosophila models with loss of sensory input, we observe non-autonomous induction of the integrated stress response (ISR) deep in the brain, as indicated by eIF2αS50 phosphorylation-dependent elevated levels of the ISR effectors ATF4 and XRP1. Unlike during canonical ISR, however, the ATF4 and XRP1 transcription factors are enriched in cytosolic granules that are positive for RNA and the stress granule markers Caprin, FMR1, and p62, and are reversible upon restoration of vision for blind flies. Cytosolic restraint of the ATF4 and XRP1 transcription factors dampens expression of their downstream targets including genes of cell death pathways activated during chronic cellular stress and thus constitutes a chronic stress protective response (CSPR). Cytosolic granules containing both p62 and ATF4 are also evident in the thalamus and hippocampus of mouse models of congenital or degenerative blindness. These data indicate a conserved link between loss of sensory input and curbed stress responses critical for protein quality control in the brain.